2020
DOI: 10.1101/gr.259069.119
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of sex-biased gene expression in the Drosophila brain

Abstract: Genes with sex-biased expression in Drosophila are thought to underlie sexually dimorphic phenotypes and have been shown to possess unique evolutionary properties. However, the forces and constraints governing the evolution of sex-biased genes in the somatic tissues of Drosophila are largely unknown. By using population-scale RNA sequencing data, we show that sexbiased genes in the Drosophila brain are highly enriched on the X Chromosome and that most are biased in a species-specific manner. We show that X-lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 63 publications
(60 reference statements)
6
40
0
Order By: Relevance
“…Although the authors conclude that this decrease is associated with the X chromosome being depauperate in genes with very high expression, even after removing overexpressed genes from the pool of analyzed genes, significant differences in the expression activity persist for intestinal tissues in males and females. The X chromosome enrichment with male-biased genes has also been shown for gene expression in the Drosophila brain [104], confirming the noted effect of selection as a factor in the evolution of sexual dimorphism.…”
Section: Discussionsupporting
confidence: 65%
“…Although the authors conclude that this decrease is associated with the X chromosome being depauperate in genes with very high expression, even after removing overexpressed genes from the pool of analyzed genes, significant differences in the expression activity persist for intestinal tissues in males and females. The X chromosome enrichment with male-biased genes has also been shown for gene expression in the Drosophila brain [104], confirming the noted effect of selection as a factor in the evolution of sexual dimorphism.…”
Section: Discussionsupporting
confidence: 65%
“…The brain comprises a major tissue type providing the neurological basis for the mating behaviors of courtship, intrasex competition, mate-choice, and post-mating male-female responses [22][23][24][25]. Sex-biased expression per se in the brain has been examined in some insects and vertebrates [3,5,22,23,[25][26][27][28][29][30][31][32]. Further, in Drosophila, analyses of a small number of neural genes have been found to be directly connected to mating functions and behaviors [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a striking paucity of data on the relationship between sex-biased expression in the brain and protein sequence evolution [22]. Moreover, the minimal research available from birds, humans and flies have suggested different types of male and female effects on rates of protein evolution, depending on the system [23,29,32] (see also some brain-related and composite-tissue analyses [36,37]), and the causes of those patterns remain poorly understood. It is therefore evident that additional study is needed of sex-biased brain expression and its relationship to molecular…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex-biased genes are unevenly distributed on the genome among various clades, especially showing enrichment on the X or Z chromosome in the homogametic sex via a pervasive phenomenon [ 11 , 12 , 62 , 63 , 64 , 65 ]. Our results exhibited that both female- and male-biased genes in both tissues were significantly enriched on the Z chromosome.…”
Section: Discussionmentioning
confidence: 99%